Analysis of Mercury (Hg) Content in Tilapia Fish (Oreochromis mossambicus) from Rawa Taliwang Lake to Enrich the Course Materials on Ecotoxicology - Irna Mulyani; M. Yamin; Khairuddin Khairuddin (Jurnal Penelitian Pendidikan IPA, 2023)
Rawa Taliwang Lake is one of the lakes in West Sumbawa Regency which is surrounded by mining. Mining waste in the form of mercury can accumulate in tilapia fish which are consumed by many people around the lake consumption of tilapia fish with mercury content can endanger health. The purpose of this study was to determine the level of mercury in tilapia fish from Rawa Taliwang Lake. This research was conducted for six months, starting from September 2022 to March 2023. Sampling was carried out using a purposive sampling method using 2 station points. The samples used were 3 fish taken from station 1 and station 2. Sample analysis was carried out in the analytical laboratory and environmental of West Nusa Tenggara using AAS (atomic absorption spectrophotometry). The part that was analyzed was the tilapia fish meat. The results of the analysis showed that the mercury content in tilapia fish from Rawa Taliwang Lake was 0.73 mg/kg which exceeded the Hg contamination limit set by the Food and Drug Supervisory Agency regulation no 9 of 2022. So tilapia fish from Rawa Taliwang Lake was unfit for consumption. The results of this study can be used as additional material in the learning process of ecotoxicology